The effect of gestational diabetes, and its treatment, on the expression of Occludin, VE-cadherin & Plakoglobin splice variants in the human placental endothelial barrier - Villota Villafuerte, Stephany D. (2019)
The placenta is essential for the development, survival and growth of the embryo, as it forms the critical interface between the fetus and the mother. Gestational diabetes mellitus (GDM) is a type of diabetes typically detected during the second or third trimester of pregnancy. Reduced occupancy of tight and adherens junctional molecules (Occludin and VE-cadherin) and disrupted junctions are a feature of human placental vessels under a diabetic milieu. Differential expression of gene splice variants and resultant protein isoforms may be behind the changes in junctional molecules and was the central hypothesis of this PhD study. The role of angiogenic growth factors and epigenetic control, if any, were also investigated in order to elucidate mechanisms behind gene expression changes. Human placental tissue from normal pregnancies were compared with those complicated by GDM where glucose levels were treated by a change of diet or by medication (metformin).